Evaluation of Dimethyl Sulfide Thresholds. (7th April 2022) - Kishnani, Prachi; Barr, Lindsay; Speers, R. Alex
Abstract: Dimethyl sulfide precursors (DMSP), present in both pilot plant floor and pneumatic malts, were used to produce craft beers and their levels were measured. The pneumatic malt was germinated at 14 °C, and the floor malt was germinated at 19.6 °C. GC analysis revealed that, on average, the pneumatic malt contained 21.5 µg DMSP/g malt, while the floor malt contained 7 µg DMSP/g malt. Difficulties with DMS sensory analyses are discussed.